VIRTUAL CURRENCIES, MICROPAYMENTS AND THE PAYMENTS SYSTEMS: A CHALLENGE TO FIAT MONEY AND MONETARY POLICY? - Verme, Paula L. Hernandez; Benavides, Ruy A. Valdes (European Scientific Journal, ESJ, 2013)
In this paper we explore the concept of virtual currencies, a concept that is fairly new not only to Economic Theory but especially to Monetary Dynamic General Equilibrium models with microfoundations. From the perspective of the conventional wisdom associated with the design and implementation of monetary policy, we are used to models where currency takes one of two forms: it is either a commodity money, from which people derive utility, or a fiat currency, whose value is mainly determined by the peopleâ€™s beliefs regarding its future acceptability in exchange for goods and services. Either of them may arise as the legal tender in the economy, and they both operate in close proximity with our every-day physical environment. However, the recent advances in electronics and telecommunications, coupled with the creation and expansion of social networks, micro-products, among other things, pose a challenge to the standard models of money. In many cases, these changes are associated with the creation of alternative and â€œvirtualâ€ realities that differ significantly from the standard physical environment of an Arrow-Debreu economy. This paper is a first and still incomplete attempt at closing the gap between these advances, their definitions and their implications for Economics as a science.